Lead exposure as a causative factor for metabolic associated fatty liver disease (MAFLD) and a lead exposure related nomogram for MAFLD prevalence - Yang, Chenyu; Li, Yuanyuan; Ding, Ran; Xing, Huiwu; Wang, Ruijue; Zhang, Mingman (Frontiers in Public Health, 2022)
The relationship between lead exposure and neurological disorders has been extensively studied, but the effects of lead exposure on hepatotoxicity are unknown. Metabolically related fatty liver disease (MAFLD) is an update of previous non-alcoholic fatty liver disease (NAFLD). It redefines the diagnostic conditions and emphasizes metabolic factors while considering non-alcoholic factors. Lead can affect the endocrine system and metabolism, so we believe that lead exposure may contribute to MAFLD. 41,723 individuals who had undergone blood lead testing from 2005 to 2018 in the NHANES database were selected for this study. The characteristics of population lead exposure in the last decade or so, the effect of lead exposure on liver function and whether lead exposure can cause MAFLD were analyzed. covariates were adjusted according to age, ethnicity, BMI, waist circumference, VAI, PIR, diabetes, hypertension, and hyperlipidemia. The results showed that blood lead concentrations stabilized at a low level after a decreasing trend from year to year. The differences in blood lead concentrations were associated with differences in age, sex, race, education level, and PIR. Lead exposure was an independent risk factor for MAFLD, and lead and nine other factors were used as independent risk factors for MAFLD, so a nomogram was established to predict the prevalence probability of MAFLD.